Toy book design: an interactionist approach about playfulness and child development - Schmidt, Marcia Cattoi; dos Santos, Célio Teodorico (InfoDesign, 2021)
Literature review article that approaches playfulness and child development based on interactionist theories. Studies in neuroscientific and physiological fields confirm that activities that involve symbolic forms develop linguistic and cognitive abilities, encourage comprehension, significance and the capability of problem solution, besides bringing emotional wellness to the child. Focused on the graphic design process, this article aims to relate the appearance of the symbolic dimension and cognitive abilities with the child interactions with singular objects as toy books, especially in the literacy period. The relationships that involve the study of knowledge representations, that is, the way the perceptions occur internally, highlighting the significance and emotion during the play. This study is part of the research in progress: "Heuristics development based on the theory of affordances to toy book design".